PEMODELAN NERACA AIR TANAH UNTUK PENDUGAAN SURPLUS DAN DEFISIT AIR UNTUK PERTUMBUHAN TANAMAN PANGAN DI KABUPATEN MERAUKE, PAPUA - Djufry, Fadjry (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2012)
Water balance modeling is one approach that can be used to predict the dynamics of soil water content for plant growth, so it can calculate the amount of crop water requirements, particularly at critical periods during which the soil moisture content is very low and in normal circumstan ces. The experiment wasconducted April-November 2010 in Merauke district of Papua provi nce. The collect ion of clim ate data (rainfall, temperature, humidity), land information(based on soil type and land use map, primarily to det ermine water holding ca pacit y and root z one depthof the soils). Land water balance analysis was con ducted for each a nalysi s of distri cts using Thornthwaite and Mather (1957). Furthermore, the results of water balance of land was mapping used the geographic information system (GIS) method for knowing the districts that have the periods of water deficit or water surplus. The results showed that the dom inant patterns of rai nfall in t he district of Merauke is pattern A is a pattern that suggests that there is a clear di fferen ce between the a mount of rai nfall duri ng th e rain y sea son t o dry season. Merauke district experienced a period of water deficit of about 4-7 months for a year. Sub districts that have a period and a high amount of water deficit isKuprik for 7 consecutive months. Sub districts that have a short period of deficit 4 months is Jagebob, Kimaan and Muting. The potential for planting food crops in Merauke district ranges from 5-7 months. The surplus per iod i s about 3-6 mont hs of November to May/June. Sub districts that have a longer period surplus isJagebob and Kimaant is 6 months. The most of the sub districts (6 sub districts) in the Merauke districthas a surplus of water> 1000 mm / year. There are only two sub districts that have surplus water <1000 mm / year is Kupri k and Sota. Sub distri cts t hatobtain high water surplus for the year is Semangga. Pot ential of th e short growing season found in Kuprik (3 months) while the potential of the growingseason is long (6 months) in almost every sub district (Semangga, Okaba, Muting Kimaan, and Sota). Water bal ance model is developed en ough valid forpredicting soil water availability and timing of food crop planting in Merauke district of Papua provinceÂ